2023
DOI: 10.7759/cureus.36204
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease in Mixed Connective Tissue Disease: An Advanced Search

Abstract: The spectrum of pulmonary manifestations associated with mixed connective tissue disease ranges from pulmonary hypertension and interstitial lung disease to pleural effusions, alveolar hemorrhage, and complications from the thromboembolic disease. Interstitial lung disease in mixed connective tissue disease is a frequently occurring entity, although in most cases it tends to be self-limited or slowly progressive. Despite this, a significant percentage of patients may present a progressive fibrosing phenotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…As in our study, the main reported causes of death are ILD and PH [19,24,25,29]. In MCTD, ILD occurs in 25%-52% patients [17,24,29,32,33] and is a matter of concern as it is responsible for pulmonary function impairment, reduced physical capacity [17], and increased mortality [39][40][41]. Regarding PH, our group has recently reported a retrospective study of 36 well-characterized patients highlighting that PH may reveal MCTD in up to a quarter of the patients, resembles SLE-and SSc-related PH, and is associated with poor survival [42].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As in our study, the main reported causes of death are ILD and PH [19,24,25,29]. In MCTD, ILD occurs in 25%-52% patients [17,24,29,32,33] and is a matter of concern as it is responsible for pulmonary function impairment, reduced physical capacity [17], and increased mortality [39][40][41]. Regarding PH, our group has recently reported a retrospective study of 36 well-characterized patients highlighting that PH may reveal MCTD in up to a quarter of the patients, resembles SLE-and SSc-related PH, and is associated with poor survival [42].…”
Section: Discussionsupporting
confidence: 58%
“…Baseline clinical and biological characteristics are detailed in Tables 1 and 2. A total of 291 patients (88.2%) were females with a median (IQR) age at diagnosis of 35 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) years. A total of 208 (63.0%) patients were Caucasian, 97 (29.4%) of Afro-Caribbean origin, and 21 (6.4%) of Asian origin.…”
Section: Patients' Characteristics At Baselinementioning
confidence: 99%
See 1 more Smart Citation
“…MCTD-PH may be associated with interstitial lung disease (ILD), and recent literature has increasingly emphasized the significant role of ILD as a contributor to morbidity and mortality among patients with MCTD-PH [ 38 ]. To mitigate the potential influence of ILD on FeNO and lung function outcomes, we excluded data from four patients with MCTD who also presented with ILD, the conclusions have not changed (the data were not listed in the table), it suggests that the presence of ILD did not significantly affect the FeNO in severe MCTD-PH patients in the manuscript.…”
Section: Discussionmentioning
confidence: 99%